Vascular Tone and Ca2+ Signaling in Murine Cremaster Muscle Arterioles In Vivo. (10th April 2013) - Mauban, Joseph R.H.; Zacharia, Joseph; Zhang, Jin; Wier, Withrow Gil
Abstract Objectives We sought to determine some of the molecular requirements for basal state "tone" of skeletal muscle arterioles in vivo, and whether asynchronous Ca2+ waves are involved or not. Methods Cremaster muscles of anesthetized exMLCK and smGCaMP2 biosensor mice were exteriorized, and the fluorescent arterioles were visualized with wide‐field, confocal or multiphoton microscopy to observe Ca2+ signaling and arteriolar diameter. Results Basal state tone of the arterioles was ~50%. Local block of Ang‐II receptors (AT1) or α1‐adrenoceptors (α1‐AR) had no effect on diameter, nor did complete block of sympathetic nerve activity (SNA). Inhibition of phospholipase C caused dilation nearly to the Ca2+‐free (passive) diameter, as did exposure to nifedipine or 2‐APB. Arterioles were also dilated when treated with SKF96365. High‐resolution imaging of exMLCK fluorescence (ratio) or GCaMP2 fluorescence in smooth muscle cells failed to reveal Ca2+ waves (although Ca2+ waves/transients were readily detected by both biosensors in small arteries, ex vivo). Conclusions Arterioles of cremaster muscle have vascular tone of ~ 50%, which is not due to α1‐AR, AT1R, or SNA. PLC activity, L‐type Ca2+ channels, 2‐APB‐ and SKF96365‐sensitive channels are required. Propagating Ca2+ waves are not present. A key role for PLC and InsP3R in vascular tone in vivo, other than producing Ca2+ waves, is suggested.